Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3390/su8020126
|View full text |Cite
|
Sign up to set email alerts
|

CSR Reporting Practices of Polish Energy and Mining Companies

Abstract: Corporate Social Responsibility (CSR) reporting receives much attention nowadays. Communication with stakeholders is a part of assumed social responsibility, thus the quality of information disclosed in CSR reports has a significant impact on fulfilment of the responsibility. The authors use content analysis of selected CSR reports to describe and assess patterns and structure of information disclosed in them. CSR reports of Polish companies have similar structures at a very high level of analysis, but a more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 17 publications
0
55
0
3
Order By: Relevance
“…The majority of research in sustainability reporting has focused on the private sector and it has been receiving increasing amounts of attention [18][19][20][21][22][23][24]. Only in recent years has an increased interest on this topic gained traction in the public sector [25][26][27][28].…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…The majority of research in sustainability reporting has focused on the private sector and it has been receiving increasing amounts of attention [18][19][20][21][22][23][24]. Only in recent years has an increased interest on this topic gained traction in the public sector [25][26][27][28].…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…So, it is very important for the company to understand and implement the concept of CSR accordingly. It is necessary to avoid potential conflicts between communities and local communities who live or have businesses around the company surroundings (Dong & Xu, 2016;Jenkins, 2004;Jenkins & Yakovleva, 2006;Szczepankiewicz & Mucko, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This review indicated that most publications related to CSR and accounting themes in Poland have focused on literature reviews, with only a few based on empirical studies (e.g., [30,31]). In contrast, the latest studies related to the issue of non-financial information in Poland have included small research samples [32,33] or have not discussed disclosures in the context of compliance with the Sustainability 2017, 9, 2304 4 of 18 requirements of the EU Directive [34][35][36]. Due to the fact that there is a lack of studies focusing on the potential contribution of the Directive to CSR disclosure in member states, especially in Poland, we decided to make this the focus of this present study.…”
Section: Introductionmentioning
confidence: 99%